The Role Of Interpersonal Communication Of Parents In Building Religious Character In The Technological Era - Syaifulloh, Rizky (Communicator: Journal of Communication, 2024)
Communication is a key element in maintaining harmony between parents and children, as parents are the first teachers of their children. Therefore, parents must set a good example to shape their children's religious character, enabling them to face various negative impacts in the digital era. One of the most commonly used forms of communication in this relationship is interpersonal communication, where interactions occur directly and allow immediate feedback from the other party.  This study employs a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation conducted by the researcher. The theoretical framework used in this study is the encoding-decoding theory by Stuart Hall. The results of the study show that the interpersonal communication conducted by parents with their children involves gradually providing understanding and giving concrete examples, making it easier for the child to comprehend. The message is then processed by the child, resulting in diverse responses, which ultimately contribute to the development of a religious character.